Addressing Ergonomics in Paddy Milling: Insights from RULA, Nordic Body Map, and Anthropometry - Rosyidi, Maulana; Sutarto, Auditya Purwandini; Izzah, Nailul (Jurnal Studi Multidisiplin Qomaruna, 2023)
A majority of the rice milling process in Indonesia has been categorized as small and medium enterprises that rely heavily on human labor during their operations. Such activities put human operators at high ergonomic risks, particularly in relation to the onset of musculoskeletal disorders (MSDs) due to postural stress, repetitive exertions, and sustained or static exertions. Ignorance of these ergonomic risk factors is likely to cause permanent disabilities in the future. As such, this study aims to identify ergonomics risk factors in the milling rice process using both the subjective method by Nordic Body Map Questionnaire and the observation method through Rapid Upper Limb Assessment (RULA). The results show that all milling rice operators reported symptoms in their shoulders and low back pain. The final score of RULA was seven or very high risk, indicating that investigation and changes are required immediately. A redesign of the existing step ladder was proposed, developed by an anthropometry-based design approach. The proposed design is expected could reduce the score to 4 or medium risk level